Association between sepsis and dementia. Issue 9 (September 2015) - Kao, Li-Ting; Sheu, Jau-Jiuan; Lin, Herng-Ching; Tsai, Ming-Chieh; Chung, Shiu-Dong
Abstract In this study, we explored the association between sepsis and dementia using a population-based dataset in Taiwan and a case-control design. The relationship between severe systemic infections and dementia is still unclear. Data for this case-control study were taken from the Taiwan Longitudinal Health Insurance Database 2000. This study included 5955 patients with dementia and 5955 sex and age-matched healthy controls. We performed conditional logistic regressions to examine the association of dementia with previously diagnosed sepsis. We found that 168 (1.41%) of the sampled people had been hospitalized for treatment of sepsis before the index date, 122 patients (2.05%) and 46 controls (0.77%; p < 0.001). The conditional logistic regression indicated that patients with dementia were more likely to have been previously diagnosed with sepsis than controls after adjusting for monthly income, urbanization level, hyperlipidemia, and diabetes (odds ratio [OR] 2.60; 95% confidence interval [CI] 1.84–3.66). We also found that dementia was associated with prior sepsis regardless of sex (males: adjusted OR 3.17; 95% CI 1.76–5.68; females: adjusted OR 2.27; 95% CI 1.48–3.47). We concluded that patients with dementia had a higher odds of previous sepsis compared to the control group.